Critical incidents as a reflective tool for professional development: an experience with in-service teachers. Issue 6 (2nd November 2018) - Yu, Wai Ming
ABSTRACT: Reflection has long been used as a professional development tool in teacher education. However, researchers have criticised that reflection is a loosely defined term and that there is little agreement on how reflection should be conducted. To achieve a more systematic application, a critical incident framework is proposed in this study and used as a reflective tool in a workshop with in-service teachers in Hong Kong. This small-scale study is based on the stories of critical incidents, journal entries and follow-up interviews provided by a sample of Hong Kong teachers. The results show that after being given the opportunity to reflect on their practices with a small community of peers, the participants showed more engaging participation in professional development and became more mindful of their ability to learn from personal experience. Moreover, after practising reflection, the teachers engaged in self-cure and used the knowledge of their previous experiences to effect changes in their classroom practices.